The correlation between neutrophil-to-lymphocyte ratio, carcinoembryonic antigen, and carbohydrate antigen 153 levels with chemotherapy-related cognitive impairment in early-stage breast cancer patients - Yu, Sheng; Zhao, Jingjing; Wang, Menglian; Cheng, Guo; Li, Wen; Tang, Lingxue; Yao, Senbang; Pang, Lulian; Yin, Xiangxiang; Jing, Yanyan; Cheng, Huaidong (Frontiers in Medicine, 2022)
Background: The changes of inflammation and tumor biomarkers are associated with the anti-tumor immunological processes. Early detection and intervention are great significance to the clinical management of cancer-related diseases. Peripheral blood biomarkers (e.g., neutrophil-to-lymphocyte ratio (NLR), carcinoembryonic antigen (CEA) and carbohydrate antigen 153 (CA153)) are obtained in real-timely, conveniently and less-invasively, and proved to availably predicte the disease states and prognosis of various cancers, including breast cancer (BC). Inflammation and poor disease management promote cognitive impairment. Chemotherapy-related cognitive impairment (CRCI) hazards long-term survival and quality of life (QOL) of BC patients, but its correlation with NLR, CEA and CA153 is not clear. Purpose: This study aimed to investigate changes in NLR, CEA and CA153 levels before and after chemotherapy and their correlation with CRCI in BC patients. Methods: The 177 BC patients who were measured for NLR, CEA and CA153 value within the first 24 hours of admission, were assigned into two groups: before/after chemotherapy group (BCG/ACG). The ACG was assigned into two subgroups based on the cognitive assessment results: cognitive normal/impaired group (CNG/CIG). Patients’ self-perceived cognitive impairments were evaluated using mini-mental state examination (MMSE), prospective and retrospective memory (PM and RM) questionnaire (PRMQ), and functional assessment of cancer therapy-cognitive function version 3 (FACT-Cog, version 3, including CogPCI, CogOth, CogPCA and CogQOL). Their QOL was also evaluated. Results: The NLR and CA153 levels were elevated after chemotherapy (BCG vs ACG: Z = -1.996 and -1.615, P = 0.046 and 0.106, respectively)， and significantly elevated in patients with CRCI (BCG vs CIG: Z = -2.444 and -2.293, P = 0.015 and 0.022; respectively). However, there was not reach significant difference in CEA levels between four groups. In addition, there was a weak to moderate correlation between peripheral blood biomarkers (NLR, CEA, and CA153) levels and CRCI (r = -0.404, -0.205, -0.322; respectively; P<0.001). Cognitive impairment scores (MMSE, PM, RM, FACT-Cog) had a strong correlation with QOL (r = -0.786, 0.851, 0.849 and 0.938; respectively; P<0.001). Conclusions: NLR and CA153 may be a valuable diagnostic adjunct of CRCI, and CRCI has a strong correlation with QOL in early-stage BC patients.